The Effect of Passing Drills and Game Situations on Passing Accuracy in Futsal Players - Muhammad Rafqi Putra; Umar Umar; Roma Irawan; Bram Sujadesman (Jurnal Gladiator, 2026)
The purpose of this study was to analyze the effect of each training method and compare the effectiveness of passing drills and game situations in improving the passing accuracy of Vamos Academy Padang futsal players. This study used an experimental method with a two-group pretest-posttest design. The research sample consisted of 20 futsal players from the Padang Vamos Academy, selected using total sampling technique, then divided into two treatment groups, namely the passing drills training group and the game situation training group. Each group was given a pre-test, treatment for 16 sessions, and a post-test. The research instrument used was a futsal passing accuracy test. The data were analyzed using descriptive statistics and t-tests after fulfilling the normality and homogeneity tests. The results showed that (1) passing drills training had a significant effect on passing accuracy (Sig. 0.000 < 0.05); (2) game situation training had a significant effect on passing accuracy (Sig. 0.000 < 0.05); (3) there was no significant difference in effectiveness between passing drills and game situation training in improving passing accuracy (Sig. 0.431 > 0.05).